Analisis Pengaruh Kinerja Keuangan Terhdap Return Saham Pada Perusahaan Indeks Lq 45Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2014 - Dimitrich, Mohammad Bella Seantikerana; , Imron Rosyadi, S.E., M.Si (2016)
The purpose of this study was to measure the impact of liquidity, solvency, and profitability to return stock in LQ 45 index of companies listed on the Stock Exchange in 2010-2014. The data used are secondary data from company financial statement derived from Indonesian Capital Market Directory (ICMD) and also determining the sample by making certain criteria. From this method were 6 companies that meet specified criteria. The amount of data that is obtained by pooling to obtain the amount of research data as much as 30. The data analysis method used is multiple regression, t test, F test, test of coefficient of determination (Adjusted R²). The results showed that: 1) the liquidity ratio (current ratio) is partially ignificant effect on return stock of -2,747 with t test was rejected at the 5% significance level. 2) the Solvency ratio (debt to equity) is partially significant effect on return stock by t test of 2,620 was rejected because less than 5%. 3) profitability ratios (return on assets) is partially significant effect on return stock by t test of 2,829 was rejected at significance level of 5%. From the regression coefficient test concluded 39,4% of the dependent variable can be explained variables, and the remaining 60,6% is influenced by other factors beyond the variables studied.